Benzylpenicillin induced specific non-IgE antibody response in mice - Zhang Lei; Wang Yong-Ming; Chen Bin-Yan; Shen Gang (Acta Pharmacologica Sinica, 2016)
AIM: To study whether or not the specific non-IgE antibody response in mice can be induced by benzylpenicillin in vivo. METHODS: Antibody response and antigenic cross reactions were determined by enzyme-linked immunosorbent assay (ELISA). Antigen molecules recognized by antibodies were tested by hapten inhibition assay. RESULTS: During d 1-d 50 after immunization, positive % of specific IgM, IgG, and IgA to benzylpenicillin were 100%, 50%-100%, and 17%-100%, respectively. IgM and IgG to benzylpenicillin also recognized ampicillin and piperacillin. The positive % of IgM and IgG to ampicillin were 23%-100% and 50%-100%, to piperacillin 43%-100% and 50%-100%, respectively. Aged benzylpenicillin showed an inhibitory effect on specific antibodies in a dose-dependent manner, and inhibitory % of specific IgM and IgG were 29%-87% and 29%-71%. However, freshly prepared benzylpenicillin had no effect. CONCLUSION: Specific non-IgE antibody response was successfully induced by benzylpenicillin in mice, in which the isotypes were mainly IgM and then IgG and IgA. Antibodies recognized degraded products, not benzylpenicillin molecule itself. Antigenic cross reactions occurred between benzylpenicillin, ampicillin, and piperacillin. Isotypes of antibodies responsible for cross reactions were mainly IgG and then IgM.